Multi-objective optimization of energy-water nexus from spatial resource reallocation perspective in China. (15th May 2022) - Zhang, Kai; Zhang, Yiyi; Xi, Shan; Liu, Jiefeng; Li, Jiashuo; Hou, Shengren; Chen, Bin
Highlights: A multi-objective energy-water nexus optimization framework is established. The provincial economic trade's impact on energy and water stress is quantified. The economic development level is the key to optimize the resources reallocation. The rapid trade growth among provinces may aggravate the risk of resource scarcity. Abstract: With China's vast territory and high regional heterogeneity in the spatial energy and water resources distribution, provincial-level embodied energy (EE) and virtual water (VW) reallocation are critical to regional energy and water recourse management but unfortunately, remain far from completed. In this paper, considering the heterogeneity of energy and water resources endowments among provinces, we constructed a dual objectives optimization framework to minimize national energy stress and water stress. Also, we evaluated the EE and VW flows' synergy impact on mitigating energy and water stress. We found that the spatial resources reallocation has a significant role on mitigating energy and water stress in high-stress regions. The results show that the net energy inflow can increase by 33.5%, and the net water inflow can increase by 42.1% in high-stress regions. The EE and VW flows' impact on mitigating resource stress is affected by the spatial resource endowments' heterogeneity. The flows that have the most positive impact on mitigating regional energy and water stress are Shanxi-Jiangsu and Jiangxi-Shanghai, respectively, while the most negative flows are Jiangsu-Henan and Xinjiang-Heilongjiang, respectively. The EE and VW flows among provinces have synergy in mitigating energy and water stress. Policy makers should not only focus on the local resources' consumption, but on the inter-provincial recourse flow and spatial resource endowments' heterogeneity. Inter-provincial cooperation is recommended, with reducing the scale of EE and VW trade that has negative impact, which can mitigate regional energy and water stress.